2022
DOI: 10.1155/2022/8170318
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Vitro/Ex Vivo Evaluation of Lecithin-Based Deformable Transfersomes and Transfersome-Based Gels for Combined Dermal Delivery of Meloxicam and Dexamethasone

Abstract: Transfersomes (TFS) are the promising carriers for transdermal delivery of various low and high molecular weight drugs, owing to their self-regulating and self-optimizing nature. Herein, we report synthesis and characterization of TFS loaded with meloxicam (MLX), an NSAID, and dexamethasone (DEX), a steroid, for simultaneous transdermal delivery. The different formulations of TFS containing varying amounts of lecithin, Span 80, and Tween 80 (TFS-1 to TFS-6) were successfully prepared by thin-film hydration met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 86 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the EE% decreased by increasing the amount of surfactant which may be due to the increase in the solubility of the drug in the aqueous phase by the increasing amount of surfactant [ 36 ]. Other researchers explained the reduction in EE% by increasing the surfactant concentration by the formation of pores in the lipid bilayer membrane which resulted in leakage of the drug [ 37 ]. The previous results were in agreement with Mayangsari et al, who prepared berberine chloride tranferosomes for transdermal use using Tween 80 as a surfactant and found that the EE% was decreased by increasing the surfactant concentration from 15% to 25% [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the EE% decreased by increasing the amount of surfactant which may be due to the increase in the solubility of the drug in the aqueous phase by the increasing amount of surfactant [ 36 ]. Other researchers explained the reduction in EE% by increasing the surfactant concentration by the formation of pores in the lipid bilayer membrane which resulted in leakage of the drug [ 37 ]. The previous results were in agreement with Mayangsari et al, who prepared berberine chloride tranferosomes for transdermal use using Tween 80 as a surfactant and found that the EE% was decreased by increasing the surfactant concentration from 15% to 25% [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hereinafter, the protein release profile data were fitted into several drug release kinetic models, namely zero-order, first-order, Higuchi, and Korsmeyer-Peppas. The data fitting model was analyzed by Microsoft Excel with DDSolver add-ins (Mazhar et al, 2023;Khan et al, 2022;Zhang et al, 2010), and the coefficient of determination (R 2 ) was used as a goodness-of-fit indicator (Costa and Lobo, 2001).…”
Section: In Vitro Protein Release Assaymentioning
confidence: 99%
“…Release studies were performed in triplicate for each sample. In order to study the drug release mechanism, the release data were fitted to zero-order, first-order, Higuchi diffusion and Koresmeyer-Peppas kinetic models, and the correlation coefficient was used as the index of goodness of fit [61,62].…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%